Front lines : soldiers' writing in the early modern Hispanic world - Martinez, Miguel (Philadelphia : University of Pennsylvania Press, Inc., 2016)
Front Lines documents the literary practices of imperial Spain's common soldiers. The epic poems, chronicles, ballads, and autobiographies that these soldiers wrote at the front provide a critical view from below on state violence and imperial expansion.
1. The Soldiers' Republic of Letters -- 2. The Truth About War -- 3. Rebellion, Captivity, and Survival -- 4. New World War -- 5. Home from War -- Epilogue.
Includes bibliographical references (pages 269-296) and index.
Print version record.
In English.
JSTOR
Keywords: Soldiers' writings, Spanish -- History and criticism; Soldiers as authors -- Spain -- History -- 16th century; Spanish literature -- Classical period, 1500-1700 -- History and criticism; Epic poetry, Spanish -- History and criticism; Soldiers in literature; War in literature; Écrits de militaires espagnols -- Histoire et critique; Militaires écrivains -- Espagne -- Histoire -- 16e siècle.; Poésie épique espagnole -- Histoire et critique; Guerre dans la littérature.; LITERARY CRITICISM -- European -- Spanish & Portuguese; Epic poetry, Spanish; Soldiers as authors; Soldiers in literature; Soldiers' writings, Spanish; Spanish literature -- Classical period; War in literature; Spain; 1500-1700; Cultural Studies; Medieval and Renaissance Studies. Literature; Electronic books; Criticism, interpretation, etc; History; Online-Ressource.